2005
DOI: 10.1128/jvi.79.4.2620-2625.2005
|View full text |Cite
|
Sign up to set email alerts
|

Civets Are Equally Susceptible to Experimental Infection by Two Different Severe Acute Respiratory Syndrome Coronavirus Isolates

Abstract: Severe acute respiratory syndrome (SARS) was caused by a novel virus now known as SARS coronavirus (SARS-CoV). The discovery of SARS-CoV-like viruses in masked palm civets (Paguma larvata) raises the possibility that civets play a role in SARS-CoV transmission. To test the susceptibility of civets to experimental infection by different SARS-CoV isolates, 10 civets were inoculated with two human isolates of SARS-CoV, BJ01(with a 29-nucleotide deletion) and GZ01 (without the 29-nucleotide deletion). All inoculat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
88
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(90 citation statements)
references
References 20 publications
2
88
0
Order By: Relevance
“…In more recent years, the use of advanced molecular techniques has enabled the identification of five novel viruses of uncertain significance. These were an orthoreovirus (mammalian reovirus MPC/04) isolated (Guan et al, 2003;Tu, 2004;Kan et al, 2005;Wu et al, 2005;Wang and Eaton, 2007) Family Orthomyxoviridae Highly pathogenic avian influenza virus H5N1 (Enurah et al, 1988a;Wilde et al, 1991;Tremlett et al, 1994;Nel et al, 2005;Susetya et al, 2008b;Pfukenyi et al, 2009;Matsumoto et al, 2011) Ikoma lyssavirus…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In more recent years, the use of advanced molecular techniques has enabled the identification of five novel viruses of uncertain significance. These were an orthoreovirus (mammalian reovirus MPC/04) isolated (Guan et al, 2003;Tu, 2004;Kan et al, 2005;Wu et al, 2005;Wang and Eaton, 2007) Family Orthomyxoviridae Highly pathogenic avian influenza virus H5N1 (Enurah et al, 1988a;Wilde et al, 1991;Tremlett et al, 1994;Nel et al, 2005;Susetya et al, 2008b;Pfukenyi et al, 2009;Matsumoto et al, 2011) Ikoma lyssavirus…”
Section: Resultsmentioning
confidence: 99%
“…Observation of clinical signs in infected individuals contributes to our understanding of pathogenicity. Detailed descriptions of clinical signs seen in viverrids were included in a small number of reports, including an investigation into morbidity or mortality in Viverridae (Roberton et al, 2006), and the documentation of experimental infection of viverrids with SARS CoV (Wu et al, 2005). However, most (Chen, 1959;Dissanaike and Paramananthan, 1961;Sachs et al, 1986;Gang et al, 1999;Aka et al, 2009;Colon and Patton, 2013;Su et al, 2013) Z, zoonotic potential acknowledged; M, platyhelminth affects multiple hosts other than Viverridae.…”
Section: Significance For Animal Healthmentioning
confidence: 99%
“…However, when palm civets were experimentally infected with 2 strains of human SARS-CoV, all developed clinical signs of fever, lethargy, and loss of aggressiveness ( 11 ). …”
Section: Role Of Masked Palm Civetsmentioning
confidence: 99%
“…Animal models described to date include several inbred mouse strains, hamsters, civet cats, ferrets, cats, or nonhuman primates (Fouchier et al, 2003; Glass et al, 2004; Greenough et al, 2005; Hogan et al, 2004; Lawler et al, 2006; Martina et al, 2003; McAuliffe et al, 2004; Qin et al, 2005; Roberts et al, 2005a; 2005b; 2007; Rowe et al, 2004a; Subbarao et al, 2004; ter Meulen et al, 2004; Wu et al, 2005). The timecourse of virus replication in these small animal models is significantly more rapid than that observed in human infections (Roberts et al, 2008) and no model fully reproduces the clinical illness or the pathology observed in humans.…”
Section: Introductionmentioning
confidence: 99%